2017
DOI: 10.1080/09168451.2017.1353405
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a β-fructofuranosidase with high transfructosylation activity from Aspergillus kawachii

Abstract: β-Fructofuranosidases belonging to glycoside hydrolase family (GH) 32 are enzymes that hydrolyze sucrose. Some GH32 enzymes also catalyze transfructosylation to produce fructooligosaccharides. We found that Aspergillus kawachii IFO 4308 β-fructofuranosidase (AkFFase) produces fructooligosaccharides, mainly 1-kestose, from sucrose. We determined the crystal structure of AkFFase. AkFFase is composed of an N-terminal small component, a β-propeller catalytic domain, an α-helical linker, and a C-terminal β-sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…It is unclear whether the two α‐glucose molecules were independently present at both subsites −2 and −1 or whether isomaltose was present as a contaminant in the glucose solution. Similar observations have been reported on GH6 cellobiohydrolases in complex with cellobiose (modeled as cellotriose and cellotetraose) and a GH32 β‐fructofuranosidase in complex with fructose (modeled as fructosylfructose) . GH31 enzymes are retaining glycosidases, and a pair of Asp residues have been identified to be catalytic residues .…”
Section: Resultssupporting
confidence: 76%
“…It is unclear whether the two α‐glucose molecules were independently present at both subsites −2 and −1 or whether isomaltose was present as a contaminant in the glucose solution. Similar observations have been reported on GH6 cellobiohydrolases in complex with cellobiose (modeled as cellotriose and cellotetraose) and a GH32 β‐fructofuranosidase in complex with fructose (modeled as fructosylfructose) . GH31 enzymes are retaining glycosidases, and a pair of Asp residues have been identified to be catalytic residues .…”
Section: Resultssupporting
confidence: 76%
“…Aspergillus aculeatus, 8,9 Aspergillus awamori, 10 Aspergillus kawachii, 11 and Aspergillus oryzae. 12 Nonetheless, the use of fungal enzymes had been shown to have some limitations because they prefer hydrolysis to transfructosylation, and most of the fungal enzymes specically synthesize only a short chain of IFOS with a degree of polymerization (DP) in the range of 2-4.…”
Section: -7mentioning
confidence: 99%
“…This enzyme was seen to be composed of an N‐terminal small component, a β‐propeller catalytic domain, an α‐helical linker, and a C‐terminal β‐sandwich. Besides, it was observed that the enzyme, like invertase 2 from A. terreus , forms a dimer (Nagaya et al, ).…”
Section: Resultsmentioning
confidence: 99%